Solid Waste Management in Indian Himalayan Region: Current Scenario, Resource Recovery, and Way Forward for Sustainable Development - Thakur, Aman; Kumari, Sareeka; Sinai Borker, Shruti; Prashant, Swami Pragya; Kumar, Aman; Kumar, Rakshak (Frontiers in Energy Research, 2021)
With the growing population, solid waste management (SWM) is becoming a significant environmental challenge and an emerging issue, especially in the eco-sensitive Indian Himalayan region (IHR). Though IHR does not host high local inhabitants, growing tourist footfall in the IHR increases solid wastes significantly. The lack of appropriate SWM facilities has posed a serious threat to the mountain-dwelling communities. SWM is challenging in the highlands due to the remoteness, topographical configuration, increasing urbanization, and harsh climate compared to plain areas. Difficulty in managing SWM has led to improper disposal methods, like open dumping and open burning of waste, that are adversely affecting the fragile IHR ecosystem. Open dumping of unsegregated waste pollutes the freshwater streams, and burning releases major pollutants often linked to the glacier melt. Processes like composting, vermicomposting, and anaerobic digestion to treat biodegradable wastes are inefficient due to the regions' extreme cold conditions. IHR specific SWM rules were revised in 2016 to deal with the rising problem of SWM, providing detailed criteria for setting up solid waste treatment facilities and promoting waste-to-energy (WtE). Despite governments' effort to revise SWM; measures like proper collection, segregation, treatment, and solid waste disposal needs more attention in the IHR. Door-to-door collection, segregation at source, covered transportation, proper treatment, and disposal are the primary steps to resource recovery across the IHR. Approaches such as waste recycling, composting, anaerobic digestion, refuse-derived fuel (RDF), and gas recovery from landfills are essential for waste alteration into valuable products initiatives like 'ban on single-use plastic' and 'polluters to pay' have a potential role in proper SWM in the IHR. Research and technology, capacity building, mass awareness programs, and initiatives like ‘ban on single-use plastic’ and ‘polluters to pay’ have a potential role in proper SWM in the IHR. This review highlights the current status of waste generation, the current SWM practices, and SWM challenges in the IHR. The review also discusses the possible resource recovery from waste in the IHR, corrective measures introduced by the government specific to IHR and, the way forward for improved SWM for achieving sustainable development of the IHR.